2013
DOI: 10.1063/1.4812230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of film thickness and air exposure on the transport gap of manganese phthalocyanine

Abstract: A consistent and accurate ab initio parametrization of density functional dispersion correction (DFT-D) for the 94 elements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Moreover, MnPc deposited on Co foil shows a small band gap opening of 0.35 eV. 25 Finally, theoretical calculations of benzene physisorbed on graphite (0001) predict as well a strong renormalization of the electronic gap. 24 In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MnPc deposited on Co foil shows a small band gap opening of 0.35 eV. 25 Finally, theoretical calculations of benzene physisorbed on graphite (0001) predict as well a strong renormalization of the electronic gap. 24 In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nominal thicknesses of the investigated CuPc films ranged from 0.5 nm to 22 nm. Films thicker than 20 nm yield no extra information for the thickness dependence study 12,25 and within this thickness range also no charging effects were found.…”
Section: Methodsmentioning
confidence: 96%
“…In essence, the electronic properties (partly) reflect the behavior of these 3d electrons, and MnPc plays a special role in the group of the transition-metal phthalocyanines. The energy gap between the occupied and unoccupied molecular orbitals of MnPc is the smallest among all transition-metal phthalocyanines [ 17 21 ], its ionization potential also is the smallest within this class of material [ 17 18 22 ], while the electron affinity is larger than those of the others [ 17 18 ]. Furthermore, the exciton binding energy related to the lowest electronic singlet excitation is somewhat larger compared to, e.g., CuPc [ 18 20 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…For MnPc, hybridized states between the Mn 3d and the ligand π orbitals give rise to physical properties different from the other phthalocyanines. For instance, MnPc shows by a small ionization potential of 4.5 eV, a large electron affinity and a small band gap . MnPc also behaves differently as compared to other transition metal phthalocyanines in view of charge transfer at interfaces or in bulk systems .…”
Section: Introductionmentioning
confidence: 99%